Photocatalytic degradation using TiO2-graphene nanocomposite under UV-LED illumination: Optimization using response surface methodology. Issue 5 (October 2019) - Fattahi, Azar; Liang, Robert; Kaur, Avneet; Schneider, Olivia; Arlos, Maricor J.; Peng, Peng; Servos, Mark; Zhou, Norman
Graphical abstract: Highlights: TiO2 -graphene nanocomposites were synthesized via a simple hydrothermal method. Response surface methodology with central composite design was used to optimize the photocatalytic efficiency of the TiO2 -graphene nanocomposites. The photocatalytic performance of the TiO2 -graphene nanocomposites were evaluated by quantifying the formation of 2-hydroxyterephthalic acid (HTPA) (probe molecule) under UV-LED illumination. The optimized nanocomposite showed 125% enhancement in photocatalytic efficiency over pure TiO2 . Abstract: Poor efficiency of TiO2 by visible light and the fast recombination rate of electron/hole pairs remain significant challenges in photocatalytic applications of TiO2 in water treatment. In this study, graphene was used to enhance TiO2 photocatalytic activity by reducing electron-hole pair recombination. Nanocomposites were formed by combining TiO2 nanoparticles (P25) with graphene oxide (GO) though simultaneous hydrothermal synthesis and GO reduction. Nanocomposite characterization confirmed that the GO was successfully reduced and P25 nanoparticles evenly dispersed in the graphene surface. The band gap of the nanocomposite was determined to be 2.74 eV, which is a promising shift to the visible spectrum in graphene-TiO2 photocatalysts. The photocatalytic performance of the TiO2 /G nanocomposites was then evaluated by quantifying the formation of 2-hydroxyterephthalic acid (HTPA) (probe molecule) under UV-LED illumination. To further optimize the photocatalytic efficiency of the TiO2 /G nanocomposites, the response surface methodology (RSM) with central composite design (CCD) was used. Out of the 6 variables including stirring time, stirring speed, the amount of TiO2, the amount of GO, hydrothermal reaction time, and ethanol/water ratio, it was determined that the last three are substantially affected the HTPA formation rate. The optimum conditions were found to be GO 0.48 wt%, ethanol/water 51.49 v/V%, and a reaction time 19 h. Predicted values for HTPA formation were found to be in good agreement with experimental values (R 2  = 0.93 and adj-R 2  = 0.87). The optimized nanocomposite showed 125% enhancement in photocatalytic efficiency over pure P25.